A Comprehensive Review of the Current Understanding and Future Directions in Biofilms and Antibiotic Resistance in Chronic Rhinosinusitis - Indra Setiawan; Miftha Churochman (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2023)
This paper aims to analyze and evaluate the impact of social media on society. The study examines about Chronic Rhinosinusitis (CRS) that is the multifactorial inflammatory disease of the nasal and paranasal mucosae for more than 12 weeks. Chronic Rhinosinusitis (CRS) is a highly widespread condition that has a significant impact on a large population around the globe. There has been a notable increase in the focus on the significance of biofilms and antibiotic resistance in the pathophysiology of chronic rhinosinusitis (CRS). The objective of this review is to consolidate existing scholarly literature on the aforementioned subjects, drawing from a selection of five prominent peer-reviewed works, while also suggesting potential avenues for further research. The objective of this study is to consolidate existing information regarding the involvement of biofilms and antibiotic resistance in the etiology and treatment of Chronic Rhinosinusitis (CRS), and to suggest potential avenues for future research. The study utilized a qualitative research methodology, integrating data from five primary scholarly papers that centered on topics such as chronic rhinosinusitis (CRS), biofilms, antibiotic resistance, and therapeutic approaches. The process involved the extraction and analysis of data in order to discover prevalent themes, inconsistencies, and areas of research that have not been adequately addressed in the current body of literature. In conclusion, it can be inferred that the given information supports the notion that biofilms have been found to have a substantial impact on the pathophysiology of chronic rhinosinusitis (CRS), leading to increased disease severity and posing difficulties in its management. Gaining comprehension of the underlying mechanisms involved in the process of biofilm formation and the development of antibiotic resistance might provide valuable diagnostic and therapeutic perspectives. Subsequent investigations ought to prioritize the advancement of therapeutic interventions targeting biofilm formation and the acquisition of a more comprehensive comprehension of the microbiome in chronic rhinosinusitis (CRS).